Macauba (Acrocomia aculeata) pulp meal as alternative raw material for growing-pigs - Dias, Estefânia Ferreira; Hauschild, Luciano [UNESP]; Moreira, Vinícius Eduardo; Caetano, Raphael Perini [UNESP]; Veira, Alini Mari [UNESP]; Lopes, Marcos Soares; Guimarães, Simone Eliza Facioni; Bastiaansen, John; Campos, Paulo Henrique Reis Furtado (Elsevier, 2021)
Macauba (Acrocomia aculeata) is an oleaginous palm native to tropical America that has received increased attention from the biofuel, food, cosmetic and pharmaceutical industries due to its high productivity and oil quality. Concomitantly, studies have suggested the potential use of macauba coproducts in ruminant feeding with still scarce information on their use in pig feeding and nutrition. The aim of this study was, therefore, to evaluate the effect of dietary macauba pulp meal on growth performance and body composition of growing pigs. To accomplish the goal, a total of 64 barrows, with 30.2 ± 1.5 kg of initial body weight (BW), were assigned to one of the four experimental diets that consisted of corn and soybean-meal based diets formulated with 0, 50, 100 or 150 g/kg of macauba pulp meal inclusion. Diets were formulated with similar metabolizable energy (ME) and crude protein (CP) content. The experimental period lasted 35 days and the pigs had free access to feed and water. Feed intake (FI) was measured and the pigs were weighed at the beginning and end of the trial to calculate their average daily gain (ADG) and feed conversion (FC). Total body minerals, fat and lean content of the pigs were assessed by dual-energy X-ray absorptiometry at the beginning and at the end of the experimental period. Data were analyzed using the GLM procedure of SAS including the fixed effects of diet and initial BW as covariate. Pigs fed with dietary inclusion of 150 g/kg of macauba pulp meal had lower FI than those fed with 0 and 50 g/kg (1,966 vs. 2,097 g/d; P< 0.01). However, macauba pulp meal inclusion did not affect ADG nor FC. Additionally, pigs fed with 150 g/kg of macauba pulp meal in the diet had greater backfat thickness than those with decreased macauba inclusion levels in the diet (P= 0.04). According to our results, macauba pulp meal could be considered as an alternative raw material to be used in the diets of growing pigs. However, its inclusion might result in animals with increased backfat thickness for the higher inclusion rates.
Keywords: Biofuels coproducts; Energy; Nutrition; Palm; Swine